2019
DOI: 10.2306/scienceasia1513-1874.2019.45.419
|View full text |Cite
|
Sign up to set email alerts
|

Detection of glyphosate resistance in black nightshade Solanum nigrum from Hunan China

Abstract: Black nightshade (Solanum nigrum) is a kind of common malignant weed in the agricultural fields worldwide. In recent years, it has not been well controlled under the commercial rate of glyphosate application in some areas of Hunan Province in China. To evaluate and confirm the glyphosate resistant biotypes of S. nigrum, the seeds of ten suspected glyphosate resistant populations of S. nigrum were collected in the agricultural fields from this province. Their GR50 values and glyphosate resistance were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition, single herbicides promoted or had no effect on the abundance of Phenylobacterium, while mixed herbicides had an effect on the abundance of Phenylobacterium. Some researchers have suggested that the combined use of GP and Cd may aggravate the effects on E. coli [42], perhaps Phenylobacterium is as sensitive as E. coli to the stress of GP combined contamination. For fungi, although GP inhibited the abundance of Talaromyces at low and medium concentrations, the addition of GP enhanced the promotion of DQ on the abundance of Talaromyces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, single herbicides promoted or had no effect on the abundance of Phenylobacterium, while mixed herbicides had an effect on the abundance of Phenylobacterium. Some researchers have suggested that the combined use of GP and Cd may aggravate the effects on E. coli [42], perhaps Phenylobacterium is as sensitive as E. coli to the stress of GP combined contamination. For fungi, although GP inhibited the abundance of Talaromyces at low and medium concentrations, the addition of GP enhanced the promotion of DQ on the abundance of Talaromyces.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strong binding property of DQ with clay particles, it is reasonable that higher levels of DQ occurred in lateritic paddy soil, which might bring more pressure on the structure and function of the microbe. Nevertheless, there are few studies on the effects of combined exposure of GP with other herbicides on microbial populations [41], where the combined toxicology of GP with other chemicals on microorganisms mainly focuses on it with heavy metals or polyethylene microplastics [42,43,44,45,46,47]. GP contains coordination groups such as carboxyl, amino, and phosphate groups, and has a strong complexing ability to heavy metal cations and organic cations [44].…”
Section: Of 15mentioning
confidence: 99%
“…Chemical fertilizers are widely used in potato cultivation; however, their excessive use has resulted in lower yield, deteriorating quality, and weakening resistance to pathogens. Longterm large-scale application of chemical fertilizers not only results in soil consolidation [1] but also leads to increasing pollution of soil, atmospheric, and aquatic systems, which severely affects further agricultural development [2][3][4]. Research studies have recently focused on fertilizer reduction and the use of alternative fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira 2020); for example, it is used intensively on soybeans (Zhang et al 2020a(Zhang et al ,2020b. In general, glyphosate has many advantages and is considered an efficient, economical and environmentally benign herbicide (Zou et al 2019). Glyphosate pathways to surface water have been studied and its dynamic transport through urban sewer systems, storm sewers, wastewater sewers and wastewater treatment plant has been described (Jiang et al 2018).…”
Section: Introductionmentioning
confidence: 99%